Clostridium butyricum Alleviates Enterotoxigenic Escherichia coli K88-Induced Oxidative Damage Through Regulating the p62-Keap1-Nrf2 Signaling Pathway and Remodeling the Cecal Microbial Community - Li, Haihua; Shang, Zhiyuan; Liu, Xuejiao; Qiao, Yingying; Wang, Kewei; Qiao, Jiayun (Frontiers in Immunology, 2021)
Clostridium butyricum (CB) can enhance antioxidant capacity and alleviate oxidative damage, but the molecular mechanism by which this occurs remains unclear. This study used enterotoxigenic Escherichia coli (ETEC) K88 as a pathogenic model, and the p62-Keap1-Nrf2 signaling pathway and intestinal microbiota as the starting point to explore the mechanism through which CB alleviates oxidative damage. After pretreatment with CB for 15 d, mice were challenged with ETEC K88 for 24 h. The results suggest that CB pretreatment can dramatically reduce crypt depth (CD) and significantly increase villus height (VH) and VH/CD in the jejunum of ETEC K88-infected mice and relieve morphological lesions of the liver and jejunum. Additionally, compared with ETEC-infected group, pretreatment with 4.4×106 CFU/mL CB can significantly reduce malondialdehyde (MDA) level and dramatically increase superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) levels in the serum. This pretreatment can also greatly increase the mRNA expression levels of tight junction proteins and genes related to the p62-Keap1-Nrf2 signaling pathway in the liver and jejunum in ETEC K88-infected mice. Meanwhile, 16S rDNA amplicon sequencing revealed that Clostridium disporicum was significantly enriched after ETEC K88 challenge relative to the control group, while Lactobacillus was significantly enriched after 4.4×106 CFU/mL CB treatment. Furthermore, 4.4×106 CFU/mL CB pretreatment increased the short-chain fatty acid (SCFA) contents in the cecum of ETEC K88-infected mice. Moreover, we found that Lachnoclostridium, Roseburia, Lactobacillus, Terrisporobacter, Akkermansia, and Bacteroides are closely related to SCFA contents and oxidative indicators. Taken together, 4.4×106 CFU/mL CB pretreatment can alleviate ETEC K88-induced oxidative damage through activating the p62-Keap1-Nrf2 signaling pathway and remodeling the cecal microbiota community in mice.